Old wine in new bottles: Validating the clinical utility of SPECT in predicting cognitive performance in mild traumatic brain injury. Issue 1 (30th January 2015) - Romero, Kristoffer; Lobaugh, Nancy J.; Black, Sandra E.; Ehrlich, Lisa; Feinstein, Anthony
Abstract: The neural underpinnings of cognitive dysfunction in mild traumatic brain injury (TBI) are not fully understood. Consequently, patient prognosis using existing clinical imaging is somewhat imprecise. Single photon emission computed tomography (SPECT) is a frequently employed investigation in this population, notwithstanding uncertainty over the clinical utility of the data obtained. In this study, subjects with mild TBI underwent 99m Tc-ECD SPECT scanning, and were administered a brief battery of cognitive tests and self-report symptom scales of concussion and emotional distress. Testing took place 2 weeks ( n =84) and 1 year ( n =49) post-injury. Multivariate analysis (i.e., partial least squares analysis) revealed that frontal perfusion in right superior frontal and middle frontal gyri predicted poorer performance on the Stroop test, an index of executive function, both at initial and follow-up testing. Conversely, SPECT scans categorized as normal or abnormal by radiologists did not differentiate cognitively impaired from intact subjects. These results demonstrate the clinical utility of SPECT in mild TBI, but only when data are subjected to blood flow quantification analysis. Highlights: SPECT perfusion is predictive of executive function in mild TBI using partial least squares. SPECT perfusion is associated with executive function in both sub-acute and chronic stages. Radiological ratings are not predictive of executive function or post-concussive symptomatology in either sub-acute or chronic stages.